Pengaruh Bauran Promosi Terhadap Keputusan Pembelian Dunkin’ Donuts Bandung - Galu Khotimatul Khusna; Farah Oktafani (Jurnal Ekonomi, Bisnis dan Entrepreneurship, 2017)
In order to be competitive a company has to offer good value propotition to the consumers. It is also necessary for company to shape good image on consumers. Dunkin Donuts is one of food and beverages company that is succeed to attract consumers to buy its products using buy 6 get 6 market branding strategy. This research aimed to analyze the impact of promotion mix to the consumers decision for Dunkin Donuts products purchase partially. Quantitative approach was designed to answer the research question. Descriptive causal analysis was used as the method of this research with questionnaire given to Bandung people for data collection. For total 385 responden, nonprobability sampling method was chosen. Data analysis was quantified using simple linear regression method. The results showed that promotion mix has positive impact on consumers decision for dunkin donuts products purchase. It could be seen that t calculated is greater than t table (16,484>1,649) using statistical significance at 0.05. According to the determination coefficient (R2) calculation  concluded that the impact value of promotion mix variable on consumers purchase decision was 41.5%. For 58.5% was influenced by other factors which was not included in this research.   Keywords: buying decision, promotion mix.